Single nucleotide polymorphism in IL1B is associated with infection risk in paediatric acute myeloid leukaemia. (June 2016) - Sung, L.; Dix, D.; Cellot, S.; Gillmeister, B.; Ethier, M.C.; Roslin, N.M.; Johnston, D.L.; Feusner, J.; Mitchell, D.; Lewis, V.; Aplenc, R.; Yanofsky, R.; et al.
Abstract: We evaluated single nucleotide polymorphisms (SNPs) associated with infection risk in children with newly diagnosed acute myeloid leukaemia (AML). We conducted a multicentre, prospective cohort study that included children aged ≤18 years with de novo AML. DNA was isolated from blood lymphocytes or buccal swabs, and candidate gene SNP analysis was conducted. Primary outcome was the occurrence of microbiologically documented sterile site infection during chemotherapy. Secondary outcomes were Gram-positive and -negative infections, viridans group streptococcal infection and proven/probable invasive fungal infection. Interpretation was guided by consistency in risk alleles and microbiologic agent with previous literature. Over the study period 254 children and adolescents with AML were enrolled. Overall, 190 (74.8%) had at least one sterile site microbiologically documented infection. Among the 172 with inferred European ancestry and DNA available, nine significant associations were observed; two were consistent with previous literature. Allele A at IL1B (rs16944) was associated with decreased microbiologically documented infection, and allele G at IL10 (rs1800896) was associated with increased risk of Gram-positive infection. We identified SNPs associated with infection risk in paediatric AML. Genotype may provide insight into mechanisms of infection risk that could be used for supportive-care novel treatments.